Propagation of ion plasma flow of cathodic arc disharge in hollow cathode (study and the first results) - Bazhenov, V.Yu.; Dobrovol’skii, A.M.; Goncharov, O.A.; Khomich, V.O.; Naiko, I.V.; Piun, V.M.; Protsenko, I.M.; Tsiolko, V.V. (Вопросы атомной науки и техники, 2016)
It is shown that the ion plasma flow originated from cathodic spots of vacuum arc discharge, at its propagation
through cylindrical electrode with proper voltage bias, initiates hollow cathode discharge, which is self-sustained
and continues its glow after the ion plasma flow blow out. At that, the hollow cathode discharge plasma features
(electron density and temperature) are mainly determined by work gas pressure and supplied electrical power.
Achieved discharge power and duration could be sufficient for efficient evaporation of microdroplets in the ion
plasma flow from vacuum arc discharge without significant loss of ion fraction of the flow. Показано, что ионно-плазменный поток из вакуумно-дугового разряда при его прохождении через
цилиндрический электрод, к которому приложено необходимое напряжение, инициирует самостоятельный
разряд с полым катодом, который продолжает гореть после прекращения ионно-плазменного потока. При
этом свойства плазмы разряда с полым катодом (плотность и температура электронов) определяются,
главным образом, давлением рабочего газа и вкладываемой электрической мощностью. Достигнутые
мощность и длительность разряда могут позволить его эффективное использование для испарения
микрокапель в плазменном потоке из вакуумно-дугового разряда без существенных потерь ионной фракции
потока. Показано, що іонно-плазмовий потік з вакуумно-дугового розряду при його проходженні через
циліндричний електрод, до якого прикладена необхідна напруга, ініціює самостійний розряд з порожнистим
катодом, який продовжує горіти після припинення іонно-плазмового потоку. При цьому властивості плазми
розряду з порожнистим катодом (щільність та температура електронів) визначаються, головним чином,
тиском робочого газу та вкладеною електричною потужністю. Досягнуті потужність та тривалість розряду
можуть дозволити його ефективне використання для випаровування мікрокрапель в плазмовому потоці з
вакуумно-дугового розряду без суттєвих втрат іонної фракції потоку.